2017
DOI: 10.18826/useeabd.336577
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of balance performance for elite male karate athletes after fatigue

Abstract: Aim: his study aimed to examine the effect of the tiredness in karate athletes, which was created with the help of a special simulation that was organized particularly to the branch in karate athletes, on the balance performance of karate athletes. Material and Methods: 16 male karate athletes were included in the study; these athletes have been doing karate for the Turkish national team and their active sports careers continue (age: 23.31±4.27 years, height: 173.4±4.91 cm, weight: 68.8±8.17 kg, BMI: 22.85±1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Balance is an important factor in combat sports performance [ 64 ]. Investigating the impact of 140 mL of beetroot juice onGreco-Roman wrestlers, Tatlici et al [ 37 ] showed supplementation improved dynamic and static balance at rest, as well as after a fatiguing stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balance is an important factor in combat sports performance [ 64 ]. Investigating the impact of 140 mL of beetroot juice onGreco-Roman wrestlers, Tatlici et al [ 37 ] showed supplementation improved dynamic and static balance at rest, as well as after a fatiguing stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest beetroot juice is a useful strategy to maintain balance performance and prevent sports injuries in combat sports. Balance is crucial in combat sports, especially in grappling contests (e.g., judo, ju-jitsu, wrestling) [ 64 ], and further investigations are required to generalize these findings for females and athletes with different competitive levels and backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found a negative moderate correlation ( r = −0.57) between the SKAT and the horizontal jumping test. Finally, balance has been considered to play an important role in karate’s activity ( Güler et al, 2017 ; Gauchard et al, 2018 ; Hadad et al, 2020 ) and martial arts in general ( Chaabene et al, 2018 ) given that it requires an effective integration of visual, vestibular, and proprioceptive inputs to transition from a dynamic to a static state ( Nardone et al, 1997 ; Young and Willey., 2010 ; Evangelos et al, 2012 ). As with CoD, sprint, and jumping performance tests, our findings showed a moderate correlation between SKAT and dynamic balance ability ( r = −0.52).…”
Section: Discussionmentioning
confidence: 99%
“…The SSp included kicking, punching, striking, and blocking moves in both stationary and variable positions. The CST included 9 exercises: (1) push up, (2) abdominal crunch, (3) vertical leg crunch, (4) jack knife, (5) supine knee drop side-to-side, (6) reverse crunch, (7) superman, (8) cat-camel stretch, and (9) plank jack (Table 1). Participants completed a 10 min warm-up including several practice trials before testing.…”
Section: Methodsmentioning
confidence: 99%
“…This martial art, which is performed in two ways called kumite and kata, is a combination of dynamic and coordinated moves that require the practitioner to give multiple reactions quickly, to attack simultaneously, and to have highly functional activity and advanced biological adaptation [3,4]. Researchers have reported that KR is a martial art in which motor and functional skills such as muscle strength, flexibility, speed, agility, balance, reaction time, coordination should be at a high level [5][6][7]. In terms of physiology, KR practitioners should have a high level of cardiorespiratory endurance, muscular endurance and anaerobic capacity.…”
Section: Introductionmentioning
confidence: 99%